Analysis and Improvement of Payroll Systems Using Agile Methods to Achieve Efficiency and Fairness - Hindarto, Djarot; Nurfaizi, Kelfin (International Journal Software Engineering and Computer Science (IJSECS), 2023)
In today dynamic business environment, the success of an organization hinges not only on the quality of its products or services but also on the efficiency and equity inherent in its employee payroll system. This research elucidates the imperative behind the transformation of corporate payroll systems in response to the rapid evolution of industry dynamics and the escalating complexity of employee requisites. The primary objective of this study is to conduct an in-depth analysis of the payroll system employed by PT Kefsone, a dynamically growing enterprise, with a specific emphasis on augmenting operational efficiency and instituting equitable compensation distribution practices. The comprehensive analysis encompasses an exploration of the evolving demands of the workforce, an evaluation of methodologies for performance assessment, and a critical review of remuneration structures and incentive policies. The findings of this research underscore the substantial impact that components affecting fairness and efficiency within PT Kefsone payroll system exert on workplace productivity, employee retention, and overall morale. Moreover, the study presents actionable recommendations for system enhancement, thoughtfully tailored to align with the company's requirements and the expectations of its workforce.